Development of a PBL E-module Integrated with Reog Ponorogo Ethnoscience to Improve Critical Thinking Skills - Siswanto, Predy; Sukarmin, Sukarmin; Utomo, Suryadi Budi (Universitas Negeri Semarang, 2025)
This research aims to develop a Problem-Based Learning (PBL) e-module inte grated with ethnoscience of Reog Ponorogo to enhance critical thinking skills. This research falls under development research, utilizing the 4D model (define, design, development, disseminate). The e-module was validated by three experts: media experts, material experts, and language experts, with six validators in each category. Additionally, a limited trial was conducted through a readability test involving two science teachers and ten seventh-grade students. The results of this research are as follows: (1) The e-module integrates local culture elements of Reog Ponorogo as learning material and is analyzed scientifically; (2) The validity results using Aiken’s formula indicate that all items were declared valid, as the calculated V value was greater than the V table (0.78) for 30 media validation items, 17 material validation items, and 9 language validation items; (3) The response results from the limited-scale readability test showed an average score of 90.5 from teachers and 87.3 from students, categorized as very good. Thus, the developed e-module has met the feasibility standards as a digital learning resource and can be tested on a larger scale to evaluate its effectiveness in improving students’ critical thinking skills.